Metabolic dysfunction-associated steatotic liver disease - Chieh Chen; Da-Ming Liao (Tungs’ Medical Journal)
As the prevalence of obesity increases globally, the incidence of metabolic dysfunction-associated steatotic liver disease (MASLD) also increases in both developed and developing countries. However, the MASLD phenotype remains unclear, with many unknown reasons. Since Ludwig and others coined the term nonalcoholic fatty liver disease in 1980, with our in-depth understanding of this condition, we gradually realized that its definition is complicated, mainly because of metabolic dysfunction. The heterogeneity of fatty liver disease and the related factors vary between individuals. The clinical manifestations and course of MASLD may be affected by multiple factors, including age, sex, race, diet, genetics, intestinal microorganisms, and environment. This study mainly searched for articles published in databases such as Cochrane Library, PubMed (Medline), UpToDate, and Google Scholar, using keywords related to digestive disease, metabolic syndrome, fatty liver, diabetes mellitus, and obesity. Case–control studies, systematic review, meta-analyses, and randomized controlled trials were also searched to explore the epidemiology and prevention of obesity or MASLD and to propose risk factors for MASLD, considering that early prevention keeps an unhealthy condition from progressing to serious chronic diseases.